Proof: Distribute Half

Let's prove the following theorem:

(a ⋅ (1 / 2)) + (a ⋅ (1 / 2)) = a

Proof:

View as a tree | View dependent proofs | Try proving it

Proof Table
# Claim Reason
1 (1 / 2) + (1 / 2) = 1 (1 / 2) + (1 / 2) = 1
2 a ⋅ ((1 / 2) + (1 / 2)) = a1 if (1 / 2) + (1 / 2) = 1, then a ⋅ ((1 / 2) + (1 / 2)) = a1
3 a1 = a a1 = a
4 a ⋅ ((1 / 2) + (1 / 2)) = a if a1 = a and a ⋅ ((1 / 2) + (1 / 2)) = a1, then a ⋅ ((1 / 2) + (1 / 2)) = a
5 (a ⋅ (1 / 2)) + (a ⋅ (1 / 2)) = a ⋅ ((1 / 2) + (1 / 2)) (a ⋅ (1 / 2)) + (a ⋅ (1 / 2)) = a ⋅ ((1 / 2) + (1 / 2))
6 (a ⋅ (1 / 2)) + (a ⋅ (1 / 2)) = a if a ⋅ ((1 / 2) + (1 / 2)) = a and (a ⋅ (1 / 2)) + (a ⋅ (1 / 2)) = a ⋅ ((1 / 2) + (1 / 2)), then (a ⋅ (1 / 2)) + (a ⋅ (1 / 2)) = a

Comments

Please log in to add comments